ChemInform Abstract: 6‐Aroylated Phenanthridines via Base Promoted Homolytic Aromatic Substitution (BHAS). Issue 21 (27th May 2014) - Leifert, Dirk; Daniliuc, Constantin Gabriel; Studer, Armido
Abstract The novel method for the synthesis of 6‐aroylated phenanthridines involves the addition of acyl radicals to the isonitrile functionality of 2‐isocyanobiphenyls and subsequent intramolecular base promoted homolytic aromatic substitution.